A Simultaneous Molecular Communication Model for Synthetic Nanodevices - Akgül, Özgür Umut; Canberk, Berk (ACM, 2014)
The molecular communication is proposed as an alternative communication technique for nanodevices. The existing challenges of nanodevice production triggered the usage of biological nanodevices, bacteria cells. However the possible dangers and the imperfect model of the biological nanodevices can cause lethal results especially when they are used in an intra-body application. Due to this reason we are proposing a synthetic nanodevice model that can be used in the intra-body applications. Even though the sizes of synthetic device model is greater than the biological nanodevices, it is stable and fully observable. These synthetic cells use molecular communication to communicate with each other. However as it is in the biological nanodevices, in synthetic nanodevices the diffusion nature of the molecules prevents the simultaneous communication, which is essential for communication. Even though the semipermable ability of the bacteria cell is usually trusted to enable unicasting, it prevents the communication between different nanodevice types. Due to this reason, such a structure can not be accepted as a simultaneous molecular communication framework. In this study, we are proposing a novel molecule filter structure that enables simultaneous communication between nanodevices. To show the practicability of the proposed framework, we also present an electronic equivalent of the designed filter. Due to the current diffuculties of implementing nanodevices in a nano-testbed in practice, we have implemented this proposed mechanism in a fully Matlab based simulation environment. The performance of the designed structure is measured in terms of interferance and number of simultaneous communication between devices.